2020
DOI: 10.1101/2020.06.04.133124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of intracellular wild-type p53 amyloids leading to cellular transformation and tumor formation in mice

Abstract: Tumor suppressor p53 mutations, with subsequent loss-of-tumor suppressive function and gainof oncogenic functions, are associated with more than 50% of human cancers. Aggregation and amyloid formation are also mechanisms by which wild type and mutant p53 might be involved in cancer, but the direct evidence of how aggregated p53 acts as an oncogene is lacking. In this study, we directly demonstrate that wild-type p53 amyloid formation imparts oncogenic properties to normal cells. Cells with p53 amyloids show en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Recent data suggest that p53 aggregation and amyloid formation is also associated with the loss of p53 tumor suppressive function and the gain of oncogenic function (Ghosh et al, 2017). Moreover, our group has recently demonstrated that p53 amyloids have prion-like properties in cells and can induce cancerous transformation in normal cells (Navalkar et al, 2020a). Although previous data suggest that p53 amyloid might be associated with cancer, the extent of p53 amyloids and cancer disease severity (such as cancer grade) is still not established yet.…”
Section: Introductionmentioning
confidence: 95%
“…Recent data suggest that p53 aggregation and amyloid formation is also associated with the loss of p53 tumor suppressive function and the gain of oncogenic function (Ghosh et al, 2017). Moreover, our group has recently demonstrated that p53 amyloids have prion-like properties in cells and can induce cancerous transformation in normal cells (Navalkar et al, 2020a). Although previous data suggest that p53 amyloid might be associated with cancer, the extent of p53 amyloids and cancer disease severity (such as cancer grade) is still not established yet.…”
Section: Introductionmentioning
confidence: 95%